Performing Brahms: Early evidence of performance style - Musgrave, Michael; Sherman, Bernard D. (Cambridge Cambridge University Press, 2003)
Although the music of Brahms is central to the lives of classical performers and listeners, few know how Brahms and his contemporaries performed his music. This study brings most of the available evidence into a single volume, along with commentary by leading Brahms experts. Most importantly, the book contains an unique CD of historic recordings--including an actual performance by Brahms--which provides tangible insight and a greater appreciation of the composer.